HPTLC Fingerprint Profiling and Preliminary Phyto-Chemical Analysis of Azadirachta Indica (Nimba) Leaf & Stem Bark. (Homoeopathy for All, 2025)
Medicinal plants have been found  useful in the cure of a number  of diseases including bacterial  diseases. Nimba is a very useful  medicinal plant in the sub-continent  and each part of the plant has  medicinal properties. Almost  every part of the plant has been in  use since ancient times to treat a  number of human ailments and  also as a household pesticide. The  extract from bark, leaves, fruits  and root have been used to control  leprosy, intestinal helminthiasis and  respiratory disorders in children.  Flavonoids, flavono glycosides,  dihydrochalcones, tannins and others  are also important constituents of  bark, leaves, fruits and flowers  of Nimba. Present study aimed at  development and establishment of  the HPTLC fingerprint profile and  phytochemical screening of Nimba  leaf and stem bark.
Keywords: Azadirachta indica; Phytochemical analysis; HPTLC fingerprinting